The experiences of family members of a person with a head injury - Iiyambo, Maria Tegelela; Small, Louis; Van Dyk, Agnes; Kamenye, Esther (International Journal of Health, 2016)
The aim of this study was to understand what the family members of a person with a head injury go through during the pre-hospitalization, hospitalization and rehabilitation period. The objective set for this study was to explore and describe the experiences of family members of a person with a head injury.A purposive sample was selected from the records of the Intensive Care Unit at the Intermediate Hospital Oshakati where the addresses of the head injury patients were identified. A qualitative explorative, descriptive and contextual research design was conducted utilizing individual in-depth face-to-face interview to gather data from family members of a person with a head injury. Data was analyzed using Tech’s method for content analysis.The results of this study showed that family members of a person with head injury had varied and different experiences varying from different feelings, challenges and support to them.Recommendations based on the findings were made for both health care providers and family members of a person with a head injury.